Actual problems of ownership of flora objects listed in the Green Book of Ukraine - Кім, Г. А. (Problems of legality, 2015)
This article is devoted to the study of issues related to the study of formation, status and trends of legal support of relations that arise out of protection, use, and reproduction of flora objects listed in the Green Book of Ukraine for the period from 1990 till the present day.